2020
DOI: 10.3390/ijerph17020398
|View full text |Cite
|
Sign up to set email alerts
|

Improving Knowledge that Alcohol Can Cause Cancer is Associated with Consumer Support for Alcohol Policies: Findings from a Real-World Alcohol Labelling Study

Abstract: Knowledge that alcohol can cause cancer is low in Canada. Alcohol labels are one strategy for communicating alcohol-related harms, including cancer. Extending existing research observing an association between knowledge of the alcohol–cancer link and support for alcohol policies, this study examined whether increases in individual-level knowledge that alcohol is a carcinogen following an alcohol labelling intervention are associated with support for alcohol polices. Cancer warning labels were applied to alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 59 publications
3
35
0
6
Order By: Relevance
“…Previous experimental and laboratory based studies have indicated that not only did AWLs displaying standard drink information and LRDG limits improve consumers’ ability to estimate recommended consumption limits ( Hobin et al, 2017 ; Osiowy et al, 2015 ), but adding labels with cancer warnings also decreased consumers’ motivation to drink ( Blackwell et al, 2018 ). Recent real-world evidence using data from subsequent waves of the current study further showed that exposure to such labels increased knowledge of alcohol–cancer risk and daily and weekly LRDG limits, and reduced overall alcohol consumption over time ( Hobin et al, 2020 ; Schoueri-Mychasiw et al, 2020 ; Weerasinghe et al, 2020 ; Zhao et al, 2020 ). Importantly, as knowledge of alcohol-related harms increases, so too does support for AWLs and other effective alcohol control measures shown to reduce alcohol harm, such as increasing minimum pricing and restricting alcohol availability and marketing; women, those who are older, and those who consume less alcohol are more likely to support such policies ( Bates et al, 2018 ; Buykx et al, 2016 ; Li et al, 2017 ; Macdonald et al, 2011 ; Moskalewicz et al, 2013 ; Pechey et al, 2014 ; Weerasinghe et al, 2020 ).…”
mentioning
confidence: 55%
“…Previous experimental and laboratory based studies have indicated that not only did AWLs displaying standard drink information and LRDG limits improve consumers’ ability to estimate recommended consumption limits ( Hobin et al, 2017 ; Osiowy et al, 2015 ), but adding labels with cancer warnings also decreased consumers’ motivation to drink ( Blackwell et al, 2018 ). Recent real-world evidence using data from subsequent waves of the current study further showed that exposure to such labels increased knowledge of alcohol–cancer risk and daily and weekly LRDG limits, and reduced overall alcohol consumption over time ( Hobin et al, 2020 ; Schoueri-Mychasiw et al, 2020 ; Weerasinghe et al, 2020 ; Zhao et al, 2020 ). Importantly, as knowledge of alcohol-related harms increases, so too does support for AWLs and other effective alcohol control measures shown to reduce alcohol harm, such as increasing minimum pricing and restricting alcohol availability and marketing; women, those who are older, and those who consume less alcohol are more likely to support such policies ( Bates et al, 2018 ; Buykx et al, 2016 ; Li et al, 2017 ; Macdonald et al, 2011 ; Moskalewicz et al, 2013 ; Pechey et al, 2014 ; Weerasinghe et al, 2020 ).…”
mentioning
confidence: 55%
“…A recent field study investigating the impact of HWLs on purchasing alcohol focused on communicating risks of cancer from alcohol consumption. These labels increased knowledge of the link between alcohol consumption and cancer, which was associated in turn with increased support for alcohol control policies such as pricing policies [49]. This study was halted due to pressure from the alcohol industry and continued without the cancer HWLs—highlighting potential challenges from industry to interventions that associate their products with health harms [50].…”
Section: Discussionmentioning
confidence: 99%
“…Consumers want and support more information on alcohol products to facilitate informed decisions [5,7]. Evidence‐informed labels such as those tested in this study have been shown to raise awareness of alcohol‐related risks and subsequently increase support for or be associated with other, more restrictive public health measures including minimum pricing and marketing and advertising restrictions, [26] and should therefore be considered as a potentially effective and important component of a broader alcohol control strategy.…”
Section: Discussionmentioning
confidence: 99%